2012
DOI: 10.1259/bjr/81849588
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography-guided ethanol ablation of predominantly solid thyroid nodules: a preliminary study for factors that predict the outcome

Abstract: The success rate of EA was 60%, and nodule vascularity and intranodular echo-staining on colour Doppler ultrasonography were useful in predicting the success rate of EA for benign, predominantly solid thyroid nodules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 26 publications
3
28
0
2
Order By: Relevance
“…This result corresponds with a previous study by this author that demonstrated that high vascularity and poor intranodular echo staining are significantly correlated with the success of EA in the treatment of benign solid thyroid nodules. 15 Moreover, remnant solid components in 2 failed cases showed a volume of Ͼ5 cm 3 before EA, while remnant solid components in 6 successful cases showed a volume of Ͻ5 cm 3 . Therefore, the author recommends the limited use of EA following incomplete RFA in cases in which the remaining component has a volume of Ͻ5 cm 3 and is not highly vascularized.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This result corresponds with a previous study by this author that demonstrated that high vascularity and poor intranodular echo staining are significantly correlated with the success of EA in the treatment of benign solid thyroid nodules. 15 Moreover, remnant solid components in 2 failed cases showed a volume of Ͼ5 cm 3 before EA, while remnant solid components in 6 successful cases showed a volume of Ͻ5 cm 3 . Therefore, the author recommends the limited use of EA following incomplete RFA in cases in which the remaining component has a volume of Ͻ5 cm 3 and is not highly vascularized.…”
Section: Discussionmentioning
confidence: 94%
“…[10][11][12][13][14] However, the author of this study has recently found that EA may be a viable alternative to RFA or surgery for the treatment of these nodules. 15 In addition, to the best of my knowledge, no study has previously examined the feasibility of using EA to remove any peripherally located solid components remaining after treatment of benign solid thyroid nodules with RFA.…”
mentioning
confidence: 99%
“…However, compared to surgical treatment or radioiodine therapy, high recurrence rates of hyperthyroidism, increase in complications, and risk of progressive regrowth make this technique indicated only for the treatment of hot nodules that cause compressing symptoms. PEI is also used in those patients presenting contraindications to or no benefits from more effective alternative treatments (1,36,44,45). The nodule decrease in volume, albeit of lower entity than in cystic nodules, is also described in literature.…”
Section: Percutaneous Ethanol Injection (Pei)mentioning
confidence: 99%
“…The procedure stops in case ethanol leakage is observed out of the nodule or if the patient refers severe pain. Some authors inject a saline solution or lidocaine during final withdrawal of the needle at the end of the procedure (36,(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50). Usually, PEI is a well-tolerated and safe technique.…”
Section: Technique and Complicationsmentioning
confidence: 99%
“…Park et al [12] reported a high incidence of malignant US features of the postsclerotic benign cystic thyroid nodules on long-term follow-up US ( Figure 6) and indicated that fibrosis may be the possible pathologic mechanism that underlies the malignant US features of these nodules. In addition, ethanol ablation is used as an alternative to thyroid surgery, radioisotope therapy, or radiofrequency ablation in the treatment of benign solid thyroid nodules [13]. A collapsing nodule after successful ethanol ablation of benign solid thyroid nodule may mimic thyroid malignancy on follow-up US (Figure 7).…”
Section: Regression After Ethanol Ablation Of Benign Thyroid Nodulementioning
confidence: 99%